THE ANXIETY LEVEL AMONG MOTHERS DURING THE COVID-19 PANDEMIC - Dewanti, Septinda Rima (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
The COVID-19 pandemic has resulted in various social and economic problems that have caused anxiety for mothers in Indonesia. The study aims to determine the difference in the level of anxiety between stay-at-home mothers and working mothers during the COVID-19 pandemic and its causes. The study was using a survey method. Two hundred seventy-six mothers completed the survey. An instrument used in the study was Beck Anxiety Inventory (BAI), while the statistical analysis used the independent sample T-test. The result shows no significant difference in the anxiety level between stay-at-home mothers and working mothers. Factors that influence the lack of difference in anxiety level include age, education level, and culture. Both working mothers and stay-at-home mothers face the same level of anxiety during the Covid-19 pandemic. We suggest providing online activities such as training activities for mothers to boost their resilience.